2015
DOI: 10.1182/blood-2013-12-547208
|View full text |Cite
|
Sign up to set email alerts
|

Both platelet- and endothelial cell–derived ERp5 support thrombus formation in a laser-induced mouse model of thrombosis

Abstract: • ERp5, like its family members PDI and ERp57, accumulates at sites of vessel wall injury.• Both platelets and endothelium secrete ERp5 on activation and contribute ERp5 necessary for thrombus formation in vivo.Protein disulfide isomerase (PDI) and endoplasmic reticulum protein 57 (ERp57) are emerging as important regulators of thrombus formation. Another thiol isomerase, endoplasmic reticulum protein 5 (ERp5), is involved in platelet activation. We show here the involvement of ERp5 in thrombus formation using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
96
1
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 65 publications
(105 citation statements)
references
References 39 publications
2
96
1
3
Order By: Relevance
“…41 Several other groups subsequently demonstrated that thiol isomerases traffic to secretory granules/membrane systems and are released from platelets in an activation-dependent manner. 36,[42][43][44][45] Kim et al showed that platelets lacking PDI have reduced activation-dependent aggregation. 46 Platelet surface PDI has been postulated to modulate a IIb b 3 function, 47 Thiol isomerases have also been found on the surface of the endothelium.…”
Section: Vascular Thiol Isomerasesmentioning
confidence: 99%
See 1 more Smart Citation
“…41 Several other groups subsequently demonstrated that thiol isomerases traffic to secretory granules/membrane systems and are released from platelets in an activation-dependent manner. 36,[42][43][44][45] Kim et al showed that platelets lacking PDI have reduced activation-dependent aggregation. 46 Platelet surface PDI has been postulated to modulate a IIb b 3 function, 47 Thiol isomerases have also been found on the surface of the endothelium.…”
Section: Vascular Thiol Isomerasesmentioning
confidence: 99%
“…69,70 Since the discovery of the importance of PDI in thrombus formation, similar observations have been extended to other thiol isomerases, including ERp57 and ERp5 (Table 2). 45,56,57 ERp57, with a domain organization parallel to PDI, is also secreted by platelets and endothelial cells on cell activation. Three groups have related ERp57 to thrombus formation using (1) blocking antibodies to ERp57 56 ; (2) genetic alterations of megakaryocyte/platelet PDIA3, 71 the gene that encodes ERp57; and (3) in vivo morpholinos in mice to decrease expression of ERp57.…”
Section: Thiol Isomerases In Thrombus Formationmentioning
confidence: 99%
“…Среди большого семейства из двадцати тиоловых изомераз к формированию тромба in vivo причастны протеин дисульфид изомераза (ПДИ) [4,7,8] и ERp57 [9][10][11][12][13]). Интегрины αIIbb3 тромбоцитов и αVb3 эндо-телия играют ключевую роль в этом процессе и напря-мую взаимодействуют с ПДИ, ERp5 и ERp57 [13].…”
Section: Thiol Isomerases As a Target For Antithrombotic Therapy тиолunclassified
“…Интегрины αIIbb3 тромбоцитов и αVb3 эндо-телия играют ключевую роль в этом процессе и напря-мую взаимодействуют с ПДИ, ERp5 и ERp57 [13].…”
Section: Thiol Isomerases As a Target For Antithrombotic Therapy тиолunclassified
See 1 more Smart Citation